Obecność motywów z Prawdziwej historii (Alethe diegemata) Lukiana z Samosat w literaturze fantastycznej na przykładzie wybranych fragmentów - Góral, Piotr (Colloquia Litteraria, 2023)
This article is an analysis the writing of Lucian of Samosata, A True Story (Alethe diegemata). Its purpose is to indicate the presence of fantastic causes in the work today and to trace the presence of the motifs used by Lucian in later fantastic writings. The dividing line between fantasy literature and science fiction is also permanently drawn, which is helpful in examining the work, as well as in an attempt to assign it to one of the revealed trends in fantasy literature.